2016
DOI: 10.1186/s12866-016-0674-y
|View full text |Cite
|
Sign up to set email alerts
|

Convenient broad-host-range unstable vectors for studying stabilization cassettes in diverse bacteria

Abstract: BackgroundLow-copy-number vectors of potential wide application in biotechnology need to encode stabilization modules ensuring their stable inheritance. The efficiency of stabilization may vary depending on the plasmid host so a thorough analysis of stabilization functions is required before use.ResultsTo facilitate such analysis highly unstable, mobilizable, broad-host-range (BHR) vectors based on RK2 replicon were constructed. The vectors are suitable for testing of various stabilization functions, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Segregational stability of pIGRK plasmid derivatives was tested by replica plating following growth under non-selective conditions for approx. Eighty generations, as described previously [40]. The incompatibility characteristics of two plasmids (residing and introduced) were examined by testing the stability of the residing replicon (pRK-1) in the presence of ampicillin in the growth medium (antibiotic selection for introduced pUC18 vector derivatives containing putative determinants of incompatibility of pIGRK).…”
Section: Methodsmentioning
confidence: 99%
“…Segregational stability of pIGRK plasmid derivatives was tested by replica plating following growth under non-selective conditions for approx. Eighty generations, as described previously [40]. The incompatibility characteristics of two plasmids (residing and introduced) were examined by testing the stability of the residing replicon (pRK-1) in the presence of ampicillin in the growth medium (antibiotic selection for introduced pUC18 vector derivatives containing putative determinants of incompatibility of pIGRK).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the contribution of each functional module to plasmid maintenance, a set of highly unstable broad-host-range plasmid vectors based on the RK2 replicon of the IncP-1 group has been constructed [ 70 ]. For example, the functionality of the partition module of a IncU plasmid ( Table 1 ), the chromosome partitioning system of Pseudomonas aeruginosa , and the hipAB TA system of the Paracoccus kondratievae plasmid have been confirmed using these vectors [ 70 ].…”
Section: Key Factors In Plasmid Designmentioning
confidence: 99%
“…It was shown that some TA systems can promote stability of plasmid maintenance due to toxin-mediated growth inhibition of plasmid-less cells [ 34 , 35 ]. Although this phenomenon is specific for plasmid-encoded TA modules, it has been also reported for several chromosomal TA systems, suggesting that their biological functions could be similar (reviewed in [ 35 ]).…”
Section: Resultsmentioning
confidence: 99%